aMussels: Diving and Anchoring in a New Bio-inspired Under-Actuated Robot Class for Long-Term Environmental Exploration and Monitoring - Donati, Elisa; van Vuuren, Godfried J.; Tanaka, Katsuaki; Romano, Donato; Schmickl, Thomas; Stefanini, Cesare (Towards Autonomous Robotic Systems, 2017)
In the last decade, the growing interest in underwater vehicles allowed significant progress in underwater robotic missions. Despite of this, underwater habitats remain one of the most challenging environments on earth due to their extreme and unpredictable conditions. The development of underwater platforms for environmental monitoring raises several challenges in terms of mobility. To monitor the huge extension of underwater habitats, vertical navigation, is needed in underwater robots. In this paper, several solutions for diving systems in a novel type of underwater robot called aMussel (artificial mussel) are investigated. These systems are: pump-based hydraulic, anchoring, a piston-type and a rolling diaphragm-based and they were compared in order to find the best trade-off between the aMussel’s requirements: low-power work regime, resistance at high pressure (2.5 bar) and geometrical constraints. The solution that best meets all the requirements is the rolling diaphragm-based system, ensuring high performance and high reliability, with low maintenance and environmental impact and an acceptable low power consumption, suggesting this to be the best way to build such under-actuated and long-term running underwater robots.